Chemical Study of ‘Harisa’, (Chili Red Pepper Sauce), Manufactured in the Libyan Arab Republic - EL-GHARBAWI, MOHAMED I. (The Libyan Journal of Agriculture, 2023)
Two different locally manufactured ‘Harisa’ (Chili red pepper sauce) were studied. Chemical and physical tests showed some significant differences with respect to their constituents. One brand product was free from any added material to the natural pepper fruit pulp extract concentrated by evaporation. The other brand product contained added filling and colouring materials in addition to chemical preservative. Some suggestions were given in this paper which could be used as a guide in the preparation of future standard specifications for the product studied.